Comprehensive training of highly qualified athletes in beach volleyball - Kostyukov V.V.; Nirka V.V.; Kostyukova O.N.; Karlitskiy I.N. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to identify the features of complex training of highly qualified athletes in beach volleyball. Methods and structure of the study. The scientific work was carried out from November 2022 to March 2023 with the participation of 24 beach volleyball players (control group - 12 people, experimental group - 12 people). For participants in the control group, the process of sports training was carried out traditionally, and for participants in the experimental group - using elements of the scientific and technological concept of complex training of athletes-players, promoting an increase in the power and intensity of the training process of beach volleyball players, an increase by 10% in the partial contribution of training exercises from the means of the fourth and the fifth training zones (heart rate during execution - 172 beats/min and above) in the total volume of training means. Results and conclusions. The results of determining the level of physical fitness of athletes and the quality of their competitive activity are presented, the average group values of which can be used as a model for those players who want to gain a foothold in leading positions in domestic and foreign beach volleyball of the highest achievements.